Optimizing Waqf Management for Community Welfare: The Strategic Role of the Indonesian Ulema Council of Bone Regency - Faisal, Muh; Hamzah, Hamzah; Ramadani, Hafilah (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
This research examines the role of the Indonesian Ulema Council (MUI) of Bone Regency in the management of waqf land as a form of social worship in Islam. Although waqf has great potential as an instrument of community empowerment, its management often faces institutional constraints. This research uses a qualitative approach through in-depth interviews and participatory observation. The findings show that MUI is active in da'wah and socialization of waqf, but has not performed its strategic function in supervision and management of waqf assets optimally. MUI's role tends to be symbolic due to limited local technical regulations, lack of collaboration with nazir, and low institutional capacity. This creates a gap between normative mandate and implementative reality. This research highlights the importance of reformulating MUI's role to function not only as a fatwa institution, but also as a strategic partner in professional, accountable, and sustainable waqf governance. The findings provide an important contribution to the literature on the role of Islamic institutions in waqf management at the regional level, as well as a basis for strengthening waqf governance based on institutional collaboration.